An audit of the effect of oxygen prescription charts on clinical practice. Issue 1012 (9th February 2010) - Wijesinghe, Meme; Shirtcliffe, Philippa; Perrin, Kyle; Healy, Bridget; James, Kate; Weatherall, Mark; Beasley, Richard
Abstract : Problem: The need to improve the prescription, administration and monitoring of oxygen therapy. Design: An interventional, prospective audit. Background and setting: Wellington Hospital, a teaching and tertiary referral hospital in New Zealand in 2007 and 2008. Key measures for improvement: Demonstration of adequate oxygen prescribing, administration and monitoring of oxygen therapy. Strategies for improvement: The introduction of a new drug chart with a specific oxygen prescription section. Targeted educational lectures primarily to medical staff. Effects of change: 610 and 566 patients were reviewed in the first and second audits. After introduction of the new oxygen prescription section on the drug chart the proportion of patients whose oxygen therapy was prescribed increased from 15/85 (17.6%) to 39/98 (39.8%), relative risk 2.3 (95% CI 1.3 to 3.9). The proportion with adequate oxygen prescription, with documentation of device, flow rate or inspired oxygen concentration, and the target oxygen saturation increased from 5/85 (5.9%) to 36/98 (36.7%), relative risk 6.2 (95% CI 2.5 to 15.0). Introduction of the new charts was not associated with changes in clinical practice in terms of assessment of oxygen saturations on room air and commencement if ≤92%, or the titration of oxygen therapy in response to oxygen saturations ≤92%. Lessons learnt: An oxygen prescription section on hospital drug charts improved the prescription of oxygen but did not improve clinical practice. Additional strategies are required to improve the administration of oxygen therapy in hospitals.